ANALISIS EFEKTIVITAS KEBIJAKAN PENGAWASAN DI BIDANG CUKAI ATAS HASIL TEMBAKAU PADA KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TIPE MADYA PABEAN A BEKASI - Tri Indah Wahyuningtyas; Dodi Rahmat Setiawan (Jurnal Ilmu Administrasi Publik, 2025)
The Customs and Excise Supervision and Service Office of Customs Type A Bekasi is one of the vertical agencies of the Directorate General of Customs and Excise that carries out supervision and services to service users receiving excise facilities. The problem faced is that the number of prosecutions and violations committed by illegal excise users is marked by the increasing circulation of illegal cigarettes which causes potential state losses. This study aims to analyse the effectiveness of supervision policies in the field of excise on tobacco products at KPPBC TMP A Bekasi as well as the obstacles and efforts made. This research uses descriptive qualitative research methods and data collection is carried out by observation, interviews and documentation. The results showed that Bekasi Customs has been quite effective in the effectiveness of supervision policies through Per-17/BC/2020 where the regulation has greatly accommodated the activities of the work unit. However, in the implementation there are still obstacles, namely the existence of resistance by violators, the limited number of officers, the low level of compliance with excise regulations, the lack of public awareness of the dangers of illegal cigarettes, and the patterns carried out by distributors of excisable goods change. Efforts made are to maximise the number of supervision officers, provide socialisation to traders about excise regulations, create new supervision patterns, provide understanding to the public of the dangers of illegal cigarettes and conduct joint operations with the Bekasi regional Satpol PP in carrying out supervision. Keywords Policy Effectiveness, Supervision, Excise, Excisable Goods of Tobacco Products, Illegal Cigarettes